An Interpretation of Edge Coloring with Special Reference to web MATHEMATICA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The concept of edge-coloring problem clearly means that we have to color all the graphical edges with the least number of colors but it should be in consideration that no two adjacent graphical edges should be given the same color. One of the most exciting new technologies for dynamic mathematics on the World Wide Web is a web Mathematica. It makes all numerics, symbolics, and graphics computing available over the web. It provides an alternative interface via the web. Even in a web environment, the front end is extremely useful. This new technology developed by Wolfram Research that allows the generation of dynamic web content with Mathematica.